Prevention and Response Strategies to Sexual Violence Against Young Children in Indonesian Localization Areas - Fajar Luqman Tri A; Oktavian Dwi Tanto (South Sulawesi Education Development (SSED), 2025)
Purpose: Sexual violence against young children constitutes a critical threat to their physical, psychological, and social development, particularly in localization areas where structural vulnerability is high. This study aims to examine and synthesize prevention and management strategies for sexual violence against early childhood in localization areas in Indonesia, with a focus on identifying effective, context-sensitive approaches for child protection. Methodology: This study employs a qualitative literature review approach. Relevant national and international scholarly articles, policy documents, and empirical studies were systematically reviewed to analyze patterns of risk, forms of intervention, and implementation challenges related to the prevention of sexual violence against young children in localization contexts. Results : The review indicates that children living in localization areas face heightened risks of sexual violence due to exposure to adult sexual activities, inadequate supervision, limited access to early childhood sexual education, and low community awareness. Effective prevention and management strategies identified include early media-based sexual education, professional training for early childhood educators, digital supervision mechanisms, and multi-sectoral collaboration among education, health, social services, and law enforcement institutions. However, implementation remains constrained by cultural resistance, limited institutional resources, and weak coordination among stakeholders. Conclusions: The findings highlight the necessity of comprehensive, integrated, and context-sensitive child protection strategies in localization areas. Preventive efforts must move beyond isolated interventions toward sustainable, multi-level approaches that combine education, professional capacity building, technological support, and inter-agency collaboration. These insights are expected to inform the development of more adaptive and effective child protection policies and practices for vulnerable early childhood populations.